Tradisi Reba dan Konservasi Uwi (Dioscorea esculenta): Kajian Etnobotani Masyarakat Adat Desa Binawali Kabupaten Ngada - Wae, Veronika P. Sinta Mbia; Nena, Anastasia Modesta; Oka, Elisabet; Surideo, Genoveva Angela (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study focuses on the Reba tradition and the conservation of yam (Dioscorea esculenta) in Binawali Village, Ngada Regency, through an ethnobotanical approach. The Reba tradition is an annual harvest ritual in which the Ngada ethnic community honors yam as a symbol of life, prosperity, and ancestral heritage. Yam is considered the